PENGARUH KOMBINASI KONSENTRASI FERMENTASI LIMBAH AIR TAHU DAN AIR CUCIAN BERAS TERHADAP PERTUMBUHAN SELADA (LACTUCA SATIVA L.) DENGAN HIDROPONIK WICK SEBAGAI RANCANGAN BOOKLET MATERI BIOTEKNOLOGI SMA - Fitria Lisni Purba; Imam Mahadi; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effect of the combination of fermented tofu waste water and rice washing water used as liquid organic fertilizer on the growth of lettuce (lactuca sativa L.) with the hydroponic wick technique. The research was carried out at the Biology Education Study Program, FKIP Riau University, Pekanbaru, November 2020 to April 2021. This study consisted of two stages, namely stage I. The combination of fermented tofu waste water and rice washing water on lettuce with a hydroponic wick using an experimental method with a factorial Completely Randomized Design (CRD) consisting of 5 treatments with 3 replications. Phase II is the design of the media booklet. Parameters observed were plant height, number of leaves, leaf width, and plant root length. Data analysis used ANOVA and DMRT Follow-up Test at 5% level. The results showed that the combination of fermented tofu waste water and rice washing water had a significant effect on the growth of plant height, number of leaves, leaf width, and root length of lettuce plants. The best concentration was in the T1B1 treatment with a concentration of 50 ml of tofu waste water and 50 ml of rice washing water. The research data was designed as a booklet for biotechnology material for class XII SMA KD 3.10 and 4.10.Key words: Waste water, tofu, rice washing water, booklets